An integrated structural health monitoring system for determining local/global responses of historic masonry buildings. Issue 8 (18th May 2018) - Blanco, Haydee; Boffill, Yosbel; Lombillo, Ignacio; Villegas, Luis
Summary: In this study, an integrated structural health monitoring system was developed and applied to a masonry heritage building under rehabilitation, where diverse structural changes were made. The late 19th century building had over the years undergone significant deterioration, which brought about the appearance of serious pathological processes affecting the building's stability. In 2012, concerns over the severe cracking phenomena affecting the structure prompted the decision to monitor the structure and to undertake strengthening interventions. A global structural monitoring system was applied to the church to identify the occurrence of possible damage mechanisms and monitoring the intervention processes. The monitoring system was based on the integration of subsystems, which were implemented as and when necessary. Traditional sensors consisting of crackmeters, servo‐inclinometers, cable extension sensors, displacement transducers, wind vanes, and temperature sensors (thermo‐hygrometer and thermocouples) were installed on the building. Moreover, novel measuring approaches using stress sensors and pressure cells were used. Furthermore, manual monitoring elements were installed, which provided measurements for contrasting with those of the continuous sensors, as well as a greater number of monitoring points. Thus, the structural response was measured using 67 monitoring elements. The long‐term (5 years) monitoring results indicated that the interventions were carried out without the occurrence of any irregularity. A good relation was confirmed between the manual and continuous measurements. Moreover, the results have shown the capability of the proposed integrated system to evaluate the structural behaviour during all the phases of the interventions.